Evaluasi Labelisasi Halal Pada Produk Dorokdok UMKM Khas Garut - Novriyanti Lubis; Vina Siti Rohimah; Tri Cahyanto; Nadia Dewi Zafirah; Lindayani Lindayani; Nenden Fauziah (Universitas Djuanda, 2026)
Dorokdok, a traditional cowhide cracker from Garut, has halal critical points involving hide origin and slaughter status, auxiliary ingredients, and contamination risks during production and storage. This study evaluated the halal certification status of dorokdok products and identified barriers encountered by micro, small, and medium enterprises (MSMEs). A descriptive approach combined field surveys, interviews with producers and retailers in Garut Regency, review of certification records, and literature analysis. The inventory identified 17 certified products or businesses and 20 uncertified ones. Reported barriers comprised perceived procedural complexity, certification costs, reliance on government-sponsored free certification programs, and limited awareness of certification requirements. The findings indicate the need for targeted technical assistance, easier access to certification services, and sustained outreach for MSMEs. Raw-material traceability and consistent halal production controls should also be strengthened so that certification provides credible halal assurance to consumers rather than merely administrative compliance